Molecular screening of microbial communities for candidate indicators of multiple metal impacts in marine sediments from northern Australia. (8th January 2016) - Cornall, Alyssa; Rose, Alea; Streten, Claire; McGuinness, Keith; Parry, David; Gibb, Karen
Abstract: Coastal sediments accumulate metals from anthropogenic sources and as a consequence industry is required to monitor sediment health. The total concentration of a metal does not necessarily reflect its potential toxicity or biological impact, so biological assessment tools are useful for monitoring. Rapid biological assessment tools sensitive enough to detect relatively small increases in metal concentrations would provide early warning of future ecosystem impact. The authors investigated in situ populations of Archaea and Bacteria as potential tools for rapid biological assessment in sediment at 4 northern Australian coastal locations over 2 yr, in both wet and dry seasons. The 1 M HCl‐extractable concentrations of metals in sediment were measured, and Archaeal and Bacterial community profiles were obtained by next‐generation sequencing of sediment deoxyribonucleic acid (DNA). Species response curves were used to identify several taxonomic groups with potential as biological indicators of metal impact. Spatial variation, sediment grain size, water depth, and dissolved oxygen also correlated with microbial population shifts. Seasonal variation was less important than geographic location. Metal‐challenge culture trials supported the identification of metal‐resistant and ‐sensitive taxa. In situ Archaea and Bacteria are potentially sensitive indicators for changes in bioavailable concentrations of metals; however, the complexity of the system suggests it is important to identify metal‐specific functional genes that may be informed by these sequencing surveys, and thus provide a useful addition to identity‐based assays. Environ Toxicol Chem 2016;35:468–484. © 2015 SETAC